Democratic Republic of Timor-Leste : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of Timor-Leste. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation highlights that Timor-Leste remains a fragile post-conflict nation with weak human and institutional capacity and large infrastructure gaps. The main challenge facing Timor-Leste is to effectively manage its petroleum wealth to reduce public-sector dependence, diversify the non-oil economy, generate jobs for a young and rapidly-growing population, and raise living standards. Political uncertainty constrained public spending in 2017-18, resulting in a sharp contraction of non-oil GDP in 2017 and flat growth in 2018. The report discusses that risks to the outlook are closely tied to the success of fiscal and structural reforms to maintain macroeconomic stability, ensure long-run fiscal sustainability, and facilitate economic diversification. The consultation recommends that a fiscal strategy should be pursued to improve expenditure control and efficiency, mobilize domestic revenue, and commit to protecting the wealth of the Petroleum Fund. Ongoing efforts to strengthen public financial management and promote good governance are crucial to ensure public investment efficiency and enhance the quality of public services.